Upscaling Potential Sustainable Agricultural Practices as Carbon Sequestration and GHG Emission Reduction Options - A. Vincent; N. Balasubramani (Journal of Agricultural Extension Management, 2021)
According to the World Resources Institute Climate Analysis Indicators Tool (WRI CAIT), India’s total Green House Gas (GHG) emissions in 2014 were 3,202 million metric tons of carbon dioxide equivalent (MtCO2e), totalling 6.55 per cent of global GHG emissions. India is the world’s fourth-biggest emitter of carbon dioxide after China, the US and the EU. In India, about 68.7 per cent of GHG emissions come from the energy sector, followed by agriculture (19.6%), industrial processes (6%), land-use change and forestry (3.8%), and waste (1.9%). The global technical GHG mitigation potential from agriculture is estimated to be 5.5-6.0 Gt CO2-eq/year, by 2030. This can be achieved by the adoption of the best available management practices related to sustainable land use, good agronomic practices, soil and water management practices, agroforestry, etc. In the COP26 summit held at Glasgow, 2021, India has pledged to adopt a net-zero emissions target by 2070. In this context, academia and research organizations are undertaking research on carbon sequestration and GHG emission mitigation. The results indicate that there are huge opportunities for investment through carbon financing in agriculture to upscale the good practices to reduce the atmospheric greenhouse gas emission through carbon sequestration. This review paper elucidates the important Climate smart Agricultural (CSA) technologies and practices that help in the sequestration of carbon and reducing the emission of GHGs